Atlas of leaf surface micromorphology in Aloe L. (Asphodelaceae) from the Horn of Africa region - Fentaw, Eshetu; Elliott, Kelda F.v.a.; Demissew, Sebsebe; Cutler, David; Grace, Olwen M. (Phytotaxa, 2021)
The confident identification to species rank of fragmentary and sterile plant material is often challenged by the absence of diagnostic characters, which are present in intact specimens, reproductive parts, and plants in habitat. Here, we consider leaf surface micromorphology for the identification of the genus Aloe in the Horn of Africa region. Primary and secondary sculpturing of the leaf epidermis and stomata were characterised from SEM micrographs of 35 taxa representing 31 species of Aloe (Asphodelaceae subfam. Alooideae). Detailed comparison revealed that leaf surface characters are conserved between species and within-species variation is modest. Closely related taxa in the Aloe adigratana—A. camperi—A. sinana species complex could be distinguished using leaf surface micromorphology alone. These characters also guide species delimitation; in the species complex including A. schoelleri and A. steudneri, a narrow circumscription is supported, whereas with A. ankoberensis and A. pulcherrima, a wider circumscription merits consideration. The observed trait combinations are characteristic of plants in xeric environments, with the most notable feature being stomata that are most deeply sunken in species in more arid habitats. Our findings support the use of comparative study of micromorphological leaf surface characters for species identification and taxonomy in the genus Aloe.